Empowerment of Newly Graduated Nurses in Six European Countries 1 Year Post-Graduation: Cross-Sectional Study and Psychometric Evaluation - Zeleníková, Renáta; Štureková, Lenka; Bujok, Petr; Leino-Kilpi, Helena; Kuokkanen, Liisa; Palese, Alvisa; Visiers-Jiménez, Laura; Brugnolli, Anna; Nemcová, Jana; Simão; De Oliveira Célia; Rua, Marília; et al. (SAGE Publications, 2026)
Introduction: Global nursing shortage emphasises empowering newly graduated nurses (NGNs) to enhance retention and satisfaction. While empowerment is widely studied, little is known about NGNs’ empowerment one year post-graduation. This study describes it and evaluates the Essential Elements of Nurse Empowerment (EENE ©Kuokkanen 2003) instrument.
Methods: 239 NGNs from six European countries responded this cross-sectional study using the EENE in 2019–2020. Data were analysed statistically.
Results: Most NGNs reported moderate empowerment. NGNs planning to stay in their workplace and profession reported higher empowerment. Exploratory factor analysis supported a four-factor structure, and the Cronbach’s alpha for the instrument was 0.88.
Discussion: Empowering NGNs is crucial for improving job satisfaction and retention. Inclusive practices and validated, culturally adaptable instruments like the EENE support equitable workforce development and culturally adaptable care. "Culturally adaptable" means retaining conceptual meaning across languages and contexts; translation revealed cultural nuances in how empowerment is understood and expressed.